Penerapan Metode Double Diamond dalam Perancangan Prototipe UI/UX Website UMKM Batik Bumiku - Sukartini Sukartini; Jemiro Kasih; Amalia Rahmah (LPPM STT Terpadu Nurul Fikri, 2026)
Batik Bumiku MSMEs are batik handicraft business actors who have been domiciled in Bogor City since 2017 and have great opportunities to grow and innovate as digital technology develops. However, limited online information and a lack of human resources in the field of technology are challenges in expanding its market reach. This research aims to design a prototype of the Batik Bumiku website as an information media while strengthening the brand image by implementing the Double Diamond method, which comprises four stages: Discover, Define, Develop, and Deliver. This process resulted in the design of the main page, including the homepage, batik catalog, batik services, and contact page. Design validation was conducted using the System Usability Scale (SUS) on the Maze platform to assess user comfort with the prototype. The evaluation results show an SUS score of 86, which is classified as very good, indicating that the design has met user expectations in both visual and usage experience. Suggestions for further development to realize the website's full potential, provide benefits that users feel, and improve mobile design to increase user accessibility.